Disruption of an ant-plant mutualism shapes interactions between lions and their primary prey - Kamaru, Douglas N. (2024)
Mutualisms often define ecosystems, but they are susceptible to human activities. Combining experiments, animal tracking, and mortality investigations, we show that the invasive big-headed ant (Pheidole megacephala) makes lions (Panthera leo) less effective at killing their primary prey, plains zebra (Equus quagga). Big-headed ants disrupted the mutualism between native ants (Crematogaster spp.) and the dominant whistling-thorn tree (Vachellia drepanolobium), rendering trees vulnerable to elephant (Loxodonta africana) browsing and resulting in landscapes with higher visibility. Although zebra kills were significantly less likely to occur in higher-visibility, invaded areas, lion numbers did not decline since the onset of the invasion, likely because of prey-switching to African buffalo (Syncerus caffer). We show that by controlling biophysical structure across landscapes, a tiny invader reconfigured predator-prey dynamics among iconic species.